The Role Of Immigration Civil Servant Investigator In The Legal History Of Indonesia - Yogi Prabowo (Journal of Law and Border Protection, 2022)
To deal with the excesses of the flow of cross-border human movement, immigration is present as an apparatus in regulating the traffic of people in and out of the territory of Indonesia, monitoring the presence and activities of foreigners while in Indonesia, as well as carrying out law enforcement activities in a sustainable and intensive manner. The legal history of Indonesia records that at first the immigration crime was a general crime which later turned into a special crime. With this paradigm change, of course, the authority of the Immigration Civil Servant Investigator will change in carrying out law enforcement. The research used in the preparation of this journal is normative legal research. Normative legal research, which can also be called doctrinal legal research, usually only uses secondary data sources, namely laws and regulations, court decisions, legal theory, and the opinions of leading scholars. Analysis of the data used is normative legal analysis because the object of this research is legislation that has permanent and binding legal force. There are 3 (three) laws and regulations that mention the role of Immigration Civil Servant Investigator in conducting criminal investigations. Immigration, namely through Emergency Law Number 8 of 1955 regarding Immigration Crimes, Law Number 9 of 1992 regarding Immigration and Law Number 6 of 2011 regarding Immigration. In each period of enactment of this regulation, the role of Immigration Civil Servant Investigator in carrying out law enforcement is increasing. It is hoped that with the increase in duties and authorities, Immigration Civil Servant Investigator can become independent Investigator in investigating immigration crimes.